HUBUNGAN KEPATUHAN KONTROL BEROBAT DENGAN TEKANAN DARAH PADA PASIEN HIPERTENSI DI UPT PUSKESMAS TAMBANG - Lara Claudia; Yenny Safitri; Rizki Rahmawati Lestari; Ridha Hidayat (Jurnal Spektrum Kesehatan Indonesia, 2025)
Hypertension is one of the major non-communicable diseases and a leading cause of death worldwide. The management of hypertension requires medication and regular blood pressure monitoring; however, patient adherence remains low. This study aimed to determine the relationship between treatment adherence and blood pressure control among hypertensive patients at UPT Puskesmas Tambang. The research employed a quantitative approach with a cross-sectional design. A total of 33 respondents were selected using accidental sampling. Data were collected through medical records and patients’ blood pressure measurements. The results showed that most patients were non-adherent to treatment (66.6%) and had uncontrolled blood pressure (72.7%). Fisher’s Exact Test yielded a p-value of 0.681 with a POR of 0.48, indicating no significant relationship between treatment adherence and blood pressure control. Nevertheless, adherent patients had a lower likelihood of experiencing uncontrolled blood pressure compared to non-adherent patients. It is recommended that healthcare providers enhance education and motivation for patients to regularly attend follow-up visits and comply with prescribed therapy. Hypertensive patients are also advised to adopt a healthy lifestyle to support treatment effectiveness.